2022
DOI: 10.3390/jpm13010099
|View full text |Cite
|
Sign up to set email alerts
|

DIGItal Health Literacy after COVID-19 Outbreak among Frail and Non-Frail Cardiology Patients: The DIGI-COVID Study

Abstract: Background: Telemedicine requires either the use of digital tools or a minimum technological knowledge of the patients. Digital health literacy may influence the use of telemedicine in most patients, particularly those with frailty. We aimed to explore the association between frailty, the use of digital tools, and patients’ digital health literacy. Methods: We prospectively enrolled patients referred to arrhythmia outpatient clinics of our cardiology department from March to September 2022. Patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Additionally, advanced age and a low level of education in patients are often identified as potential obstacles to the widespread use of such solutions [ 25 ], as well as a source of anxiety and alienation [ 38 ] feelings that are exacerbated by the inherent impersonality of digital services [ 34 ]. In specific settings, such as heart failure, atrial fibrillation, and stroke, characterized by advanced age [ 51 , 52 , 53 ], frequently associated with frailty and disability [ 43 ], regarding the lack of digital literacy [ 54 ], the involvement of caregivers and family members may be an option to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, advanced age and a low level of education in patients are often identified as potential obstacles to the widespread use of such solutions [ 25 ], as well as a source of anxiety and alienation [ 38 ] feelings that are exacerbated by the inherent impersonality of digital services [ 34 ]. In specific settings, such as heart failure, atrial fibrillation, and stroke, characterized by advanced age [ 51 , 52 , 53 ], frequently associated with frailty and disability [ 43 ], regarding the lack of digital literacy [ 54 ], the involvement of caregivers and family members may be an option to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the unavailability of resources in health systems overwhelmed with COVID-19 cases may have resulted in lower likelihood of hospitalization. Patients manifesting with milder symptoms may have been managed in the outpatient setting, owing to the rapid increase in the availability and utilization of virtual visits [ 21 ]. Additionally, it has been reported that the COVID-19 pandemic caused interruptions in services, including diagnostic testing, which may have contributed to decreased diagnosis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%